Efektifitas Kinerja Pegawai dalam Meningkatkan Pelayanan Administrasi pada Bagian Umum Sekretariat Daerah Kabupaten Batu Bara - M. Zikri Arifin; Marlon Sihombing; Heri Kusmanto (Mahesa Research Center, 2022)
The purpose of the study was to analyze the effectiveness of employee performance in improving administrative services at the General Section of the Regional Secretariat of Batu Bara Regency. To analyze the efforts and barriers to the effectiveness of employee performance in improving administrative services at the General Section of the Regional Secretariat of Batu Bara Regency. The form of this research is descriptive qualitative where this research focuses on the process, description of the analysis, which aims to find out about the effectiveness of employee performance in improving administrative services at the General Section of the Regional Secretariat of Batu Bara Regency. The results of the study show that the ineffective and efficient performance of employees in the general department in the distribution of correspondence results in sluggish performance and delays in the process of an organization in regional apparatus. In terms of administrative services, it still shows that the administrative services for distributing correspondence within the Regional Secretary are carried out by General Section employees. So that the apparatus only responds mediocrely in the form of administrative services both responsibly, communication and responsively, not so well received.